Single-Color Fluorescence Lifetime Cross-Correlation Spectroscopy In Vivo - Štefl, Martin; Herbst, Konrad; Rübsam, Marc; Benda, Aleš; Knop, Michael (Biophysical journal, 2020)
The ability to quantify protein concentrations and to measure protein interactions in vivo is key information needed for the understanding of complex processes inside cells, but the acquisition of such information from living cells is still demanding. Fluorescence-based methods like two-color fluorescence cross-correlation spectroscopy can provide this information, but measurement precision is hampered by various sources of errors caused by instrumental or optical limitations such as imperfect overlap of detection volumes or detector cross talk. Furthermore, the nature and properties of used fluorescent proteins or fluorescent dyes, such as labeling efficiency, fluorescent protein maturation, photostability, bleaching, and fluorescence brightness can have an impact. Here, we take advantage of previously published fluorescence lifetime correlation spectroscopy which relies on lifetime differences as a mean to discriminate fluorescent proteins with similar spectral properties and to use them for single-color fluorescence lifetime cross-correlation spectroscopy (sc-FLCCS). By using only one excitation and one detection wavelength, this setup avoids all sources of errors resulting from chromatic aberrations and detector cross talk. To establish sc-FLCCS, we first engineered and tested multiple green fluorescent protein (GFP)-like fluorescent proteins for their suitability. This identified a novel, to our knowledge, GFP variant termed short-lifetime monomeric GFP with the so-far shortest lifetime. Monte-Carlo simulations were employed to explore the suitability of different combinations of GFP variants. Two GFPs, Envy and short-lifetime monomeric GFP, were predicted to constitute the best performing couple for sc-FLCCS measurements. We demonstrated application of this GFP pair for measuring protein interactions between the proteasome and interacting proteins and for measuring protein interactions between three partners when combined with a red florescent protein. Together, our findings establish sc-FLCCS as a valid alternative for conventional dual-color fluorescence cross-correlation spectroscopy measurements.
Keywords: Fluorescence; Luminescent Proteins; Green Fluorescent Proteins; Fluorescent Dyes; zelené fluorescenční proteiny; luminescentní proteiny; fluorescenční barviva; fluorescenční spektrometrie; Spectrometry, Fluorescence; fluorescence